Problem Based Learning (PBL) Model on Students' Environmental Literacy Ability in Elementary School Natural Science Lessons: Model Problem Based Learning (PBL) Terhadap Kemampuan Literasi Lingkungan Siswa pada Pelajaran Ilmu Pengetahuan Alam Sekolah Dasar - Ilma, Mukhibatul; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2023)
This study aims to analyze the influence of problem based learning (PBL) models on students' environmental literacy skills in elementary science lessons.This study uses a pre-experimental quantitative research with a one-group pretest posttest design. The population in this study were all students of class V SDN Watukosek totaling 21 students. Samples were taken using saturated sampling with a sample of 21 students in class V SDN Watukosek. Data collection techniques used in the form of tests. Where this test is carried out before learning (pretest) and after learning (posttest). Where this test is carried out before learning (pretest) and after learning (posttest). The instrument used in this research is a matter of environmental literacy indicators. The analysis used is calculated using the N-Gain formula with the average pretest and posttest values of 56.38 and 81.26 while the N-Gain score is 0.56 in the medium category. Based on the results of this study, it can be concluded that the PBL model has an effect on students' environmental literacy skills in elementary science lessons.